Кибернетические модели в управлении качеством отливок - Пелых, С. Г.; Пономаренко, Ольга Ивановна (Информационно-издательский дом "ЦентрИнформ", 2006)
Повышение качества и конкурентоспособности отливок является в настоящее время важнейшей научной и практической задачей литейного производства. В настоящее время основным методом практического решения задач, связанных с повышение качества литья, является совершенствование технологических процессов их изготовления на базе прикладных исследований, разработки новых инженерно-технологических идей и математических моделей физико-математического характера. Однако этот подход имеет ограниченные возможности, а в его рамках не может быть достигнут рыночный уровень качества отливок.

Improving the quality and competitive capacity of casting is currently the most important scientific and real-world problem for foundry. Today the main approach in a real-world problem solving is working the process of castings manufacture on the base of applied research, development brand new engineering ideas and mathematical models of physico-mathematical nature. Although this approach has constrained capabilities and the market quality of the castings can’t be achieved within its frame. Taking into account the peculiarities of achieving the casting quality, the complexity of control and multi-level process of its forming, it is expedient to apply system analysis and cybernetic models as its key instrument. Regular-style casting design, appropriate manufacturing technique and well-handled production process will add to creating a high-quality technology. Insufficient work timing, out-of-balance condition capacity, unreliable manufacturing equipment may result in growth of rejected castings number. Some experiments, which have been made at Kupyansk foundry and Kharkiv tractor plant, are described below in the article.
Cybernetic models in quality control of casting
Keywords: деталь литая; напряжения механические; литье высококачественное; система формовочно-смесеприготовительная; агрегативная математическая модель; оборудование формовочное